Influência da pandemia COVID-19 e da atividade física sobre Síndrome de Burnout, qualidade de vida e percepção da aprendizagem online em estudantes de ciências agrárias - Azzi, Diana Vilela (2022)
The COVID-19 pandemic has brought about a drastic and unexpected change around the world, requiring social distancing measures with strong consequences on the education system. A large portion of schools and colleges had to quickly join the emergency remote teaching system (ERE). The impacts of these actions are still poorly understood. In higher education specifically, most of the studies carried out involve students from courses in the area of human health. However, other groups such as students of Veterinary Medicine and the greater area of Agrarian Sciences are also exposed to similar environmental factors. Mental health changes have been considered public health problems in the pandemic world and, therefore, of extreme relevance not only in the professional scope but also in academic environments. This thesis was divided into two chapters: 1) Longitudinal study, comparing the risk of Burnout Syndrome (BS), the frequency of physical activity and the academic effectiveness of students of veterinary medicine and other courses in the area of Agrarian Sciences before and during the COVID-19 pandemic. Seventy-seven college students responded to an online questionnaire. The emotional exhaustion domain showed significant improvement over time in women who reported practicing physical activity. A similar effect was observed for the disbelief domain for both men and women. Academic effectiveness increased over time without interference from sex factors or physical activity. There was no influence of the modality of the undergraduate course. 2) Cross-sectional study with students from all over Brazil in order to assess the prevalence of SB, Quality of Life (QoL), frequency of physical activity and perception of online learning (OL) during the COVID-19 pandemic, considering sociodemographic characteristics and area of the undergraduate course (Agrarian Sciences, Health Sciences, Human and Social Sciences, Exact Sciences). Cluster analysis was used to determine groups of individuals with similar characteristics. Three different profiles of students were observed: group with “low QOL” (composed of younger students, mainly female, with a higher frequency of psychological disorders, in addition to higher Burnout scores, lower QOL and worse perception of OL); group with “intermediate QoL” (comprised of participants aged approximately 45 years, mainly men, married, with children and who worked in addition to studying); and the “high QL” group (composed of students with higher scores in all domains of the QOL questionnaire, better perception of OL, higher frequency of physical activity and lower scores on the SB questionnaire). The results showed significant differences between the major areas of knowledge, in which students from the health area had better scores in psychological domains in relation to the other areas. Students in the areas of Exact Sciences showed better performance in relation to OL. In general, from the analysis of the two chapters, it was possible to conclude that the practice of regular physical activity can be an important tool in the prevention of mental health changes in university students of Veterinary Medicine and Agrarian Sciences. It was surprisingly observed that academic performance improved as well as the risk of SB reduced during the pandemic. However, it was observed that younger students and mainly female students had a higher frequency of psychological disorders, higher risk of SB, worse QOL and worse OL. Such findings provide subsidies for educational managers to draw up strategic plans to face academic difficulties during the pandemic period.